Management of Whiteflies, Whitefly-Vectored Plant Virus, and Insecticide Resistance for Vegetable Production in Southern Florida - David J. Schuster; Philip A. Stansly; Jane E. Polston; Phyllis R. Gilreath; Eugene McAvoy (EDIS, 2007)
ENY-735, a 4-page fact sheet by David J. Schuster, Philip S. Stansly, Jane. E. Polston, Phyllis R. Gilreath, and Eugene McAvoy, describes improved recommendations developed by the Resistance Management Working Group for the control of the whiteflies and reducing insecticide resistance. Includes links to additional information and references and a table with information for selecting insecticides for whitefly management programs. Published by the UF Entomology and Nematology Department, March 2007.